2016
DOI: 10.1002/ange.201511733
|View full text |Cite
|
Sign up to set email alerts
|

Basic Physicochemical Properties of Polyethylene Glycol Coated Gold Nanoparticles that Determine Their Interaction with Cells

Abstract: Ahomologous nanoparticle library was synthesized in which gold nanoparticles were coated with polyethylene glycol, whereby the diameter of the gold cores,a sw ell as the thickness of the shell of polyethylene glycol, was varied. Basic physicochemical parameters of this two-dimensional nanoparticle library,s uch as size, z-potential, hydrophilicity, elasticity,a nd catalytic activity ,were determined. Cell uptake of selected nanoparticles with equal size yet varying thickness of the polymer shell and their effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…At present, hyaluronan’s local administration is applied in arthrology, ophthalmology, and esthetic medicine, 17 , 18 but its systemic application is highly challenging due to rapid blood clearance 19 22 and susceptibility to hydrolysis. In this respect, hyaluronan-based therapeutics might benefit from nanomedicine-based formulation strategies, which have shown their tunability for cellular interactions 23 and profound impact on the pharmacokinetic properties of various biomaterials. 24 , 25 Although hyaluronan has been deposited on the surface of either lipid or polymeric nanoparticles, studies exploiting the polymeric backbones of hyaluronan for nanoparticle assembly, which can be achieved by chemical modification of hyaluronan carboxyl groups, are scarce.…”
mentioning
confidence: 99%
“…At present, hyaluronan’s local administration is applied in arthrology, ophthalmology, and esthetic medicine, 17 , 18 but its systemic application is highly challenging due to rapid blood clearance 19 22 and susceptibility to hydrolysis. In this respect, hyaluronan-based therapeutics might benefit from nanomedicine-based formulation strategies, which have shown their tunability for cellular interactions 23 and profound impact on the pharmacokinetic properties of various biomaterials. 24 , 25 Although hyaluronan has been deposited on the surface of either lipid or polymeric nanoparticles, studies exploiting the polymeric backbones of hyaluronan for nanoparticle assembly, which can be achieved by chemical modification of hyaluronan carboxyl groups, are scarce.…”
mentioning
confidence: 99%
“…Physicochemical properties of nanocarriers such as size, 51,52 shape, 51 surface charge 53,54 and hydration shell, 55 are known factors modulating bio-nano interaction including cellular binding, uptake, protein surface binding, [13][14][15][16] and toxicity. To investigate cell interactions of polymeric micelles, hydrophobically modified Rhodamine B dye was encapsulated by co-precipitation during self-assembly.…”
Section: Nano-bio Interaction (Cellular Uptake)mentioning
confidence: 99%
“…Nonspecific binding of plasma proteins like albumin or complement factors to nanoparticles ("corona formation"), [12][13][14][15][16] induction of and binding to preformed IgM, 17,18 and nonspecific binding of nanoparticles to cells are well known, [19][20][21] and such nano-bio interactions are believed to be fundamentally influenced by surface properties at the molecular level and the nanoscale level. Surface properties may include molecular polymer structure, presence and distribution of hydrophobic domains 22 and charged residues 23 in the surface layer, formation of secondary or tertiary structure by the polymer (as shown for PEG 24 ) and nanoscale topology of the nanoparticle surface.…”
mentioning
confidence: 99%
“…Physicochemical properties of nanocarriers such as size, 51,52 shape, 51 surface charge 53,54 and hydration shell, 55 are known factors modulating bio-nano interaction including cellular binding, uptake, protein surface binding, [13][14][15][16] Observational studies have reported that surface charges of nanoparticles are important for nanobio interactions. [56][57][58] We therefore investigated the structure-function relationship of charged groups, charge parameters, and cell interaction in more detail using the synthetic and modeling information.…”
Section: Nano-bio Interaction (Cellular Uptake)mentioning
confidence: 99%
“…A proper understanding of the interaction of plasma proteins with nanoparticles is of great importance for their successful application in nanomedicine. [13][14][15][16] Due to the interactions between nanoparticles and proteins, the conformation of proteins may alter and novel epitopes may be From the above phenomena, the interaction between HSA and polymeric micelles is highly dependent on the terminal charge and hydrophilic length (PMOXA) of copolymer. Therefore, hydrophobic interaction, electrostatic interaction, even hydrogen bonds play a role in the binding processes.…”
Section: Nano-bio Interaction (Effect Of Chemistry and Shape On Plasmmentioning
confidence: 99%